Determinants of Economic Growth in Selected African Oil Producing Countries - Farag Gaballa; Nazatul Haron (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2025)
This study aims to examine the impact of oil revenue, non-oil revenue, and oil prices on economic growth in five African oil-producing economies, Nigeria, Angola, Algeria, Libya, and Egypt, over the period 1970 to 2020. The study applied second-generation econometric techniques, including the Cross-sectional Im–Pesaran and Cross-sectional Augmented Dickey-Fuller tests, Westerlund panel cointegration, the CS-ARDL model, and Dumitrescu and Hurlin heterogeneous panel Granger causality. The results reveal cross-sectional dependence and slope homogeneity among the countries. Panel unit root tests indicate that all variables are stationary at first difference, while cointegration tests confirm a long-run equilibrium relationship. Empirical evidence shows that oil revenue, non-oil revenue, and oil prices significantly influence economic growth, with bidirectional causality between these variables and growth. These findings highlight the need for economic diversification by expanding non-oil revenue sources and implementing supportive policies to sustain long-term growth. The study recommends that policymakers prioritize investment in non-oil sectors and strengthen domestic participation in oil production to foster inclusive and sustainable development.